The Effect of Audio Media on Short Story Listening Comprehension Among Third-Grade Elementary Students - Dirham Dirham; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence, 2026)
This research was prompted by the less than optimal short story listening comprehension skills of third-grade students at SD Negeri 105 Adian Jior, Mandailing Natal Regency. This research employed a quantitative approach with a quasi-experimental design, specifically the Pretest-Posttest Control Group Design. The study sample consisted of two groups: an experimental class (Class III B) and a control class (Class III A), each comprising 25 students. Data collection was conducted through written tests (pre-test and post-test) consisting of 5 multiple-choice questions designed to measure short story listening comprehension. The test instrument was piloted and met validity criteria (all items rcount > rtable = 0.396) and reliability (Cronbach's Alpha = 0.720 > 0.600), and demonstrated good difficulty levels, discriminative power, and effective distractor functions. Data analysis used the Independent Samples T-Test after fulfilling the normality and homogeneity assumptions. The results showed a significant improvement in short story listening comprehension in the experimental class compared to the control class. In the experimental class, which used audio media, the average post-test score for short story listening comprehension reached 80.8 (pre-test score 62.4), with a highest score of 96 and a lowest score of 64. Meanwhile, in the control class, which used conventional methods, the average post-test score was 65.6 (pre-test score 60.8), with a highest score of 76 and a lowest score of 48. The Independent Samples T-Test results showed a significance value (2-tailed) of 0.000. Since the Sig. (2-tailed) value was < 0.05, the Null Hypothesis (H0) was rejected and the Alternative Hypothesis (H1) was accepted. This research concludes that the use of audio media has a significant effect on improving short story listening comprehension in third-grade students of SD Negeri 105 Adian Jior, Mandailing Natal Regency, during the 2025-2026 Academic Year